Integration of Realia Media and the Scientific Approach in Strengthening Students’ Scientific Attitudes: A Systematic Literature Review - Yunianto, Lilik Bangun; Suryandari, Kartika Chrysti; Triyani, Septi (Universitas Sebelas Maret, 2026)
Meaningful science learning requires active student engagement supported by contextual media. This study aims to analyze the use of realia media through the scientific approach and its contribution to strengthening students’ scientific attitudes. A systematic literature review following the PRISMA protocol was conducted. Of 52 identified articles, 26 met the inclusion criteria and were analyzed. The findings show that integrating realia media with the scientific approach enhances student engagement, conceptual understanding, and science process skills. It also promotes scientific attitudes such as curiosity, honesty, accuracy, openness to evidence, and responsibility. However, challenges include teacher readiness, classroom management, and limited instructional time. Overall, this study confirms that the integration of realia media and the scientific approach is an effective strategy for strengthening scientific attitudes in elementary IPAS learning.